Structural Analysis In The Fairy Tale “Hänsel”Und Gretel” And “Golden Cucumbers” - Siahaan, Dhela Adinda R.P; Purba, Lydia; Simanjuntak, Tarida Alvina (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to describe the structure of the fairy tales